DAMPAK SOSIAL PERUSAHAAN TERHADAP PERILAKU MASYARAKAT - Dian Wahyuni K. Bali (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
Printing business as part of manufacture industry needs to allocate half of its total asset for the current asset to run its operation. PT XYZ, one of national printing companies,suffers from its working capital due to high account receivable. Obtaining 70% funding from the external loan to finance its operation creates the company paying high interest. The purpose of this paper is (1)to attempt an assessment of the company financial performance from liquidity, solvability, cash ratio, degree of operating leverage, degree of financial leverage dan degree of total leverage point of views (2) to study the company’s working capital and (3) to analyze working capital factors and other factors which influence to the Debt To Total Asset. The approach of this study is a quantitative using PT XYZ’s audited financial reports. Sales and financial ratio analysis including liquidity ratio, solvability, cash ratio, degree of operating leverage, degree of financial leverage and degree of total leverage are used in this research. The result of the research analysis has shown that from the liquidity and cash ratio aspects, the company is struggle to pay from short term of current liabilities. Based on the data of solvability aspects, loan ratio is increasingto more than 50% or 137% from the total loan ratio. However, data from the degree of operating ratio, degree of financial leverage and the degree of total leverage reveals that the company used its high operating dan financial leverage which influence the EBIT and EAT.The increasing number of 69% of short term liabilities and the use of 70% of external funding indicate that the company use its working capital aggressively. Therefore the significant variables which influence to solvability ratio are Account receivable period (X1), inventory period (X3), the growth of fixed asset (X4) and account payable period (X5), other factor such as sales (X2) and degree of total leverage (DTL) did not significantly influence to the solvability ratio (Debt to Total Asset)